(untitled) - Rau, Alan Scott (New York, NY, 2006)
Murray, Rau and Sherman’s casebook provides detailed information on processes of dispute resolution. The casebook provides the tools for fast, easy, on-point research. Part of the University Casebook Series®, it includes selected cases designed to illustrate the development of a body of law on a particular subject. Text and explanatory materials designed for law study accompany the cases
Keywords: Dispute resolution (Law),Sự giải quyết tranh chấp; United States,Hoa Kỳ